Peranan Pustakawan Dalam Sistem Temu Balik Informasi di Perpustakaan Sekolah SMA N 1 Bukit Sundi - Monica Zahara; Muhammad Fadhli (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
The main problem in this thesis is the role of the librarian in improving the information retrieval system in the school library of SMA N 1 Bukit Sundi. This study aims to identify and explain the role of librarians in information retrieval systems, and what obstacles are faced by librarians and users in information retrieval systems.The research method used in this research is the method qualitative research using descriptive type. Collection technique The data used are observation, interviews, and documentation. Technique The data analysis used is data reduction, data presentation, data withdrawal conclusion and verification. Guarantee the validity of the data in this study using triangulation of techniques, sources and time. The results of the study concluded that the librarian plays an important role in the information retrieval system. The role of the librarian in the information retrieval system is generally in the processing section such as cataloging, classifying library materials, and determining subject headings to facilitate data entry and information retrieval in the retrieval system. In addition, in terms of processing library materials, book inventory activities, labeling, barcode attachment, and book bag attachment are also carried out. In the service section, the librarian's role is more about returning and borrowing library materials,provide guidance to users regarding procedures for information retrieval, use of libraries, use of independent services and librarians also serve users if someone comes directly to ask the librarian about the information needed quickly and accurately. Librarians also act as educators (educators) as educational librarians, providing education such as mini-meetings once a year to provide education to users on how to use catalogs, managers, administrators, and also supervisors in information retrieval systems.Keywords: Librarian, Retrieval System